2023
DOI: 10.1007/s10461-023-04019-x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Towards Treatment as Prevention Among PrEP-Experienced Gay and Bisexual Men in Australia

Abstract: The introduction of HIV pre-exposure prophylaxis (PrEP) has the potential to impact the attitudes gay and bisexual men (GBM) who consequently choose to take PrEP have towards treatment as prevention (TasP), and the extent to which they are willing to have condomless anal intercourse (CLAI) with an HIV-positive sexual partner who has an undetectable viral load (UVL). Using a cross-sectional sample from an observational cohort study conducted from August 2018 to March 2020, we examined the extent to which PrEP-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Our results showed the highest level of confidence in relying on U=U recorded to date among GBM in Australia. 26,27,29 Consistent with previous research, we found that knowledge of and belief in U=U was concentrated among people living with HIV, followed by PrEP users. 15,23 The lowest levels of familiarity, perceived accuracy and willingness to rely upon U=U were among HIV-negative and untested men who were not using PrEP (some of the groups who might benefit from greater knowledge of U=U).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results showed the highest level of confidence in relying on U=U recorded to date among GBM in Australia. 26,27,29 Consistent with previous research, we found that knowledge of and belief in U=U was concentrated among people living with HIV, followed by PrEP users. 15,23 The lowest levels of familiarity, perceived accuracy and willingness to rely upon U=U were among HIV-negative and untested men who were not using PrEP (some of the groups who might benefit from greater knowledge of U=U).…”
Section: Discussionsupporting
confidence: 90%
“…25 Previous Australian research has not evaluated familiarity with the specific U=U message or its perceived accuracy. Previous research has assessed the willingness of Australian GBM to have condomless sex with a partner living with HIV who has an undetectable viral load, and found low levels of willingness, [26][27][28][29] particularly among HIV-negative and untested men who do not use PrEP. However, most of this research was conducted before the U=U campaign gathered momentum and did not explicitly ask participants whether they were familiar with the U=U message, believed in its accuracy, or were willing to rely upon an undetectable viral load when having condomless sex with partners living with HIV.…”
Section: Introductionmentioning
confidence: 99%